2000
DOI: 10.1001/archfami.9.4.327
|View full text |Cite
|
Sign up to set email alerts
|

Part-time Physicians: Physician Workload and Patient-Based Assessments of Primary Care Performance

Abstract: Part-time physicians perform as well as full-time physicians in most aspects of primary care, including all interpersonal aspects of care, as reported by patients. Patients of physicians working more than 65 hours per week experienced higher levels of visit-based continuity of care than patients of physicians working fewer hours, but this appears to carry a cost to those physicians in the area of personal and professional satisfaction. Subsequent research should examine the relationship between physician workl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 17 publications
1
57
0
1
Order By: Relevance
“…Participants who worked less than 40 hours were designated part-time. 10 Part-time orientation was ascertained by soliciting attitudes about part-time jobs in medicine, including the consequences of working part-time on cooperation, teamwork, and intent to decrease hours. For this analysis, we included all Dutch respondents (n ϭ 1976) still practicing medicine.…”
Section: Methodsmentioning
confidence: 99%
“…Participants who worked less than 40 hours were designated part-time. 10 Part-time orientation was ascertained by soliciting attitudes about part-time jobs in medicine, including the consequences of working part-time on cooperation, teamwork, and intent to decrease hours. For this analysis, we included all Dutch respondents (n ϭ 1976) still practicing medicine.…”
Section: Methodsmentioning
confidence: 99%
“…We found empirical evidence consistent with the argument that full-time physicians provide better access and continuity of care. [9][10][11][12]16 However, contrary to much of the The physician was the unit of analysis. The left out variables include: % 19≤Age<35, % Non-Hispanic White, % PPO, and the Division Two Indicator.…”
Section: Discussionmentioning
confidence: 99%
“…15 Despite these concerns, only one study included empirical evidence and found that PCPs working greater than 65 h/week had slightly higher continuity, but no difference in access. 16 Furthermore, the patient perspective on being cared for by a part-time PCP is not well understood. One systematic review concluded that provider work hours had no relationship with patient satisfaction, [16][17][18] yet because of the lack of welldesigned studies, the authors could not make strong conclusions about these findings.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations